Combined Periodontal and Endodontic Management of Palatal Radicular Groove with Platelet-Rich Fibrin and Biodentine® - Arjun Hari Rijal; Bhageshwar Dhami; Pratistha Ghimire (Case Reports in Dentistry)
Palatal radicular groove (PRG) is developmental anomaly of root, which when present is associated with periodontal and endodontic problems. Different treatment modalities are available for its management, such as periodontal flap surgery, endodontic management, sealing of PRG with various cements, bone graft procedure for intrabony defect, extraction with intentional replantation after sealing or removal of a PRG, and endodontic treatment as well as the use of various growth factors. Success of the therapy depends on the type, depth, and extent of PRG, presence or absence of intrabony defect, vitality of involved tooth, and types of materials used to seal PRG. This study reports management of PRG with Biodentine® and platelet-rich fibrin in a 44-year-old systemically healthy female patient.